2006
DOI: 10.1103/physrevlett.97.082502
|View full text |Cite
|
Sign up to set email alerts
|

KIsomers inNo254: Probing Single-Particle Energies and Pairing Strengths in the Heaviest Nuclei

Abstract: We have identified two isomers in 254No, built on two- and four-quasiparticle excitations, with quantum numbers K pi = 8- and (14+), as well as a low-energy 2-quasiparticle Kpi = 3+ state. The occurrence of isomers establishes that K is a good quantum number and therefore that the nucleus has an axial prolate shape. The 2-quasiparticle states probe the energies of the proton levels that govern the stability of superheavy nuclei, test 2-quasiparticle energies from theory, and thereby check their predictions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 28 publications
6
61
0
Order By: Relevance
“…The decay of 254 No was recently revisited by Herzberg et al [13] and by Tandel et al [14], where a second isomer was found. In the nucleus 252 No, a new K isomer with a half-life of 110 ± 10 ms at an excitation energy of 1254 keV was discovered at SHIP (GSI, Darmstadt) [15] and confirmed at FMA (Argonne National Laboratory) [16], both experiments using decay spectroscopy techniques.…”
Section: Introductionmentioning
confidence: 97%
“…The decay of 254 No was recently revisited by Herzberg et al [13] and by Tandel et al [14], where a second isomer was found. In the nucleus 252 No, a new K isomer with a half-life of 110 ± 10 ms at an excitation energy of 1254 keV was discovered at SHIP (GSI, Darmstadt) [15] and confirmed at FMA (Argonne National Laboratory) [16], both experiments using decay spectroscopy techniques.…”
Section: Introductionmentioning
confidence: 97%
“…For example, β 2 ≈ 0.27 has been derived for 254 No from the measured ground-state band [6]. The observation of K isomers with highly hindered decays in 254 No [7][8][9] points to an axially symmetric shape for the nucleus. The deformation can bring the single-particle levels from the next shell across the predicted closure down to the Fermi surface.…”
mentioning
confidence: 98%
“…a coupling of the two 8 − configurations built on two protons and two neutrons, respectively, which are expected to lie close in energy. However, in [10], a proposal of 14…”
Section: Systematics Of Isomers Above Z = 82mentioning
confidence: 99%
“…While isomers in this region have been known for many years, e.g., in 250 Fm and 254 No [8], a breakthrough came when detailed spectroscopy of 254 No revealed the presence of two isomers, whose decay path included a twoquasiproton (1/2 − [521] × 7/2 − [514]) 3+ configuration. This showed that the 3f 5/2 orbital which in spherical nuclei would lie above the postulated magic gap at Z = 114 lies close to the Fermi surface in well-deformed nuclei in the nobelium region and is available for study [9,10]. Since then a wealth of experimental information has been gathered on isomers in this region in nuclei reaching up to 270 Ds [11,12].…”
Section: Introductionmentioning
confidence: 99%